A genome assembly for Orinus kokonorica provides insights into the origin, adaptive evolution and further diversification of two closely related grass genera - Kunjing Qu; Ai Liu; Mou Yin; Wenjie Mu; Shuang Wu; Hongyin Hu; Jinyuan Chen; Xu Su; Quanwen Dou; Guangpeng Ren (Communications Biology, 2023)
Abstract Ancient whole-genome duplication (WGD) or polyploidization is prevalent in plants and has played a crucial role in plant adaptation. However, the underlying genomic basis of ecological adaptation and subsequent diversification after WGD are still poorly understood in most plants. Here, we report a chromosome-scale genome assembly for the genus Orinus (Orinus kokonorica as representative) and preform comparative genomics with its closely related genus Cleistogenes (Cleistogenes songorica as representative), both belonging to a newly named subtribe Orininae of the grass subfamily Chloridoideae. The two genera may share one paleo-allotetraploidy event before 10 million years ago, and the two subgenomes of O. kokonorica display neither fractionation bias nor global homoeolog expression dominance. We find substantial genome rearrangements and extensive structural variations (SVs) between the two species. With comparative transcriptomics, we demonstrate that functional innovations of orthologous genes may have played an important role in promoting adaptive evolution and diversification of the two genera after polyploidization. In addition, copy number variations and extensive SVs between orthologs of flower and rhizome related genes may contribute to the morphological differences between the two genera. Our results provide new insights into the adaptive evolution and subsequent diversification of the two genera after polyploidization.